Smart grid interoperability maturity model - Jing ZHOU; Guojun LIU; Ziwei HU; Lifeng LU; Wei ZHANG (Dianxin kexue)
Smart grid interoperability is a kind of ability that a set of electrical equipments and systems exchange and share information safely,seamlessly and transparently with standard interface.The Grid Wise Architecture Council（GWAC）sponsors using concepts from capability maturity models in the software industry to smart grid interoperability and has been drafted an interoperability maturity model which is being in the project verification stage.The interoperability requirements of the smart grid and the work of the GWAC working group to promote interoperability maturity model（IMM）were analyzed.The evaluation and analysis of the maturity of the smart grid interoperability were studied and discussed.It would effectively help the development of smart grid planning from the dimensions of strategy and tactics to consider the interoperability of smart grid.